Appearance of Chance Coincidence in Attenuation Measurements Carried out by using Coincidence Technique - Mahmoud A. Elawi; Rasha W. Klaib; Khalid H. Mehdi (Tikrit Journal of Pure Science, 2022)
The appearance of chance coincidence in attenuation measurements using coincidence technique is investigated. A two 3"*3" NaI(Tl) detector coincidence spectrometer with 0.5 μ Ci Na-22 source were used. Two different materials with different forms, namely mixed metallic powders and Fe-sheets are used. The ratio of chance counts to total real coincidences in annihilation peak had ranged between (0.007-0.013) and (0.011-0.036) for the different thicknesses of the two materials mentioned respectively. The coincidence linear attenuation coefficients due to the chance coincidence at 1274keV were 0.1 and 0.38 cm-1 for the two materials assuring the proportionality with energy. When the chance coincidence counts were treated as being "lost" from real coincidences and added again to the latter, no change were observed in attenuation coefficient at annihilation peak from that calculated before taking accidental counts into consideration.